Investigation of the association between the TCF7L2 rs7903146 (C/T) gene polymorphism and obesity in a Cameroonian population: a pilot study - Aurelie Nguimmo-Metsadjio; Barbara Atogho-Tiedeu; Jean Jacques Noubiap; Marie-Solange Evehe; Rosine Djokam-Dadjeu; Olivier Sontsa Donfack; Dieudonne Nanfa; Edith Pascale M. Mato; Elvis Ndonwi Ngwa; Magellan Guewo-Fokeng; Priscille Pokam-Fosso; Wilfred F. Mbacham; et al. (BMC, 2017)
Abstract Objective This study aimed at investigating the association between the rs7903146 (C/T) polymorphism of the TCF7L2 gene with obesity in a Cameroonian population. Method This was a case-control pilot study including 61 obese and 61 non-obese Cameroonian adults. Anthropometric indices of obesity, blood pressure, fasting blood glucose, and blood lipids were measured. The rs7903146 (C/T) polymorphism of the TCF7L2 gene was genotyped using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP), and genotypes were correlated with clinical and biological parameters. Results The T allele was predominant in the study population with a frequency of 93%. No statistically significant difference was however observed between the genotypic (p = 0.50) and allelic frequencies (p = 0.58) of obese and non-obese subjects. Comparison of clinical and biochemical parameters of C allele carriers (CX = CC + CT) with those of TT genotype showed that there was no significant difference between the lipid profile of these two groups. Conclusion The rs7903146 (C/T) polymorphism of the TCF7L2 gene might not be associated with obesity in the Cameroonian population.